WORK-RELATED EMOTIONAL EXHAUSTION AND ITS MANIFESTATIONS - Sadiqova Gulbarno; Umarkulova Madina (Journals Park Publishing, 2024)
The article contains information about work-related emotional fatigue and its manifestations, burnout syndrome, views of scientists, psychological diseases that can be caused by fatigue as a complication of work-related problems.
Keywords: emotional exhaustion, burnout, work, problem, health, illness, symptom, person, methods, mental, symptom, syndrome.